Determinants Factor of Passengers’ Propensity to Utilize E-hailing Services in Kota Kinabalu, Sabah - Darawati, Azwa Safiqah; Ladin, Mohd Azizul (International Journal of Integrated Engineering, 2024)
The utilization of public transportation in Kota Kinabalu has declined as more people rely on private vehicles. This worsened traffic congestion, transportation delays, and air pollution. The expanding number of mobile transportation applications from transportation network firms has raised demand for E-hailing, also known as transportation network companies (TNCs). E-hailing services have quickly gained popularity and widespread use, displacing traditional taxi services by allowing millions of journeys every day. People choose e-hailing because public transit lacks the comfort and convenience of private vehicles, while taxis lack the affordability and transparency of app-based e-hailing. The aim of this study is to identify the determinants factor of passengers’ propensity to utilize e-hailing services in order to have a better understanding of the situation among Kota Kinabalu residents. The Stated Preference Survey (SPS) method was used in this study. A questionnaire was created and disseminated online to 300 respondents to obtain the necessary information. The data was analyzed using the Chi-square test and descriptive analysis. The finding shows that price, safety, convenience and accessibility are found to be a good predictor on Kota Kinabalu residents’ factors to utilize e-hailing service whereby significant relationship (p-value